Understanding the acceptance of engineered bamboo technology among furniture producers: An application of an extended UTAUT framework - Lantican, Carl Anthony Ordanes (Animo Repository, 2022)
With the current push of the Philippine government to bamboo as a greener and more sustainable alternative to wood various programs and initiatives were made to develop the industry. The engineered bamboo technology was introduced to help transform traditional bamboo poles into a more functional composite material comparable to traditional wood/ lumber. Despite these, the industry has been lagging from its expected growth and industrywide acceptance. Several reports attributed it to the lack of the intended producers (furniture and craft makers) who are willing to utilize the technology to produce for end-consumers. Through an extensive literature review, it became apparent that theoretical paradigms of technology acceptance may change for any given environment and technological context. Without a formal study on the technology acceptance of engineered bamboo among its intended adoptors, this research banked on the robustness of the UTAUT model to explain the phenomena and determine the drivers of technology acceptance. It also reconciled information from the limited qualitative studies that brought out new concepts to be analyzed: (1) resistance to change, (2) trust in the technology, (3) personal innovativeness, and (4) absorptive capacity. From a pilot study demonstrating the similar framework, the interconnection of commercial considerations and performance expectations to the technology was developed, thus, the need for further examination. Its mediating effect between the UTAUT constructs and behavioral intention to adopt the engineered bamboo technology was also investigated. A total of 171 responses were received and was analyzed through structural equations modelling. The produced model was able to explain substantive (R2=78.50%) variations in the behavioral intention, which is superior against previous similar studies. Results show that performance expectancy, absorptive capacity, effort expectancy, personal innovativeness, resistance to change and commercial uncertainty were significant predictors of technology acceptance intention, ranked according to their impact. Digging deeper via the IPMA and NCA, results suggest that TT, SI, and FC, which were initially found to be statistically insignificant, were in fact necessary factors to cause a high level of behavioral intention. Social Influence was also found to have indirect effect to the acceptance intention through commercial uncertainty, signaling the importance of market factors affecting the intention of technology acceptance. Results of the study was able to offer new knowledge in the field of technology acceptance by creating a new model in understanding behavioral paradigms. Business implications and recommendations were formulated accordingly.